PENGARUH INSENTIF, DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN TOKO ANYAR NGANJUK - Septiani, Lia; Wihara, Dhiyan Septa; Leksono, Poniran Yudho (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
In facing competition in this era of globalization, companies are required to work more efficiently and effectively in order to maximize the expansion of the business world and improve employee performance. The purpose of this study is to analyze (1) Incentives have a significant effect on the performance of Nganjuk Anyar Shop employees. (2) Discipline has a significant effect on the performance of Nganjuk Anyar Store employees. (3) Work experience has a significant effect on the performance of Nganjuk Anyar Store employees. (4) Incentives, Discipline, and work experience simultaneously have a significant effect on the performance of Nganjuk Anyar Store employees. The population in this study were the employees of the Friends of Nganjuk Building Materials Store. Respondents in this study were 40 using the total sampling method. And analyzed by Multiple linear regression with the help of the SPSS Version 29 application. The conclusions from this study are (1) Incentives partially have a significant effect on the performance of Nganjuk Anyar Store employees. (2) Discipline partially has a significant effect on the performance of Nganjuk Anyar Store employees. (3) Work experience partially has a significant effect on the performance of Nganjuk Anyar Store employees. (4) Incentives, Discipline, and work experience simultaneously have a significant effect on the performance of Nganjuk Anyar Store employees